Measurement of proportional piling and narrative experience on food security assessments in Bera Pahang, malaysia. / Siti Zubaidah Muhamad Hasbulah - Muhamad Hasbulah, Siti Zubaidah (2016)
Food security or rather insecurity is a term employed to describe the adequacy of food access that will meets people food preferences as well as their dietary need in term of physical and economic access. It is a basic cause of malnutrition and mortality and important factor in the longer term livelihood security. This study was conducted on August 2015 for nearly one month at Bera District of Pahang which involve 12 villages that comprise high risk area as well as low risk area in order to assess food security during emergency situation. The purpose of this study is (1) to measure the proportional piling for food security assessment during flood disaster and (2) to identify the relationship between mapping and chronology to food security. This study has been done by using mixed method. In determining the measurement of proportional piling, quantitative study involving cross-sectional design was conducted. Whereas qualitative study was conducted by using retrospective design in order to assess experience and chronological event of study population during flood disaster. Methodologies are also depended on rapid assessment techniques such as interviews, observation, mapping, chronology and proportional piling. The data on qualitative parts was presented narratively. Upon the completion of data analysis on proportional piling, approximately 47.2% (n=50) drinking water as their significant source to sustain lives during emergency flood situation. While fast and dry food encompassed of 34.9% (n=37), the second highest needs that was preferred by respondent across Bera District. The neighborhood’s lives in flooded zone has been found as well prepared and develop their own approaches to overcome the upcoming flood calamity. This is evidenced through their preparation in terms of food stock as well as build high shelf inside their house to save their household goods. As conclusion, the food security assessment should be conducted during emergency situation to prevent the occurrence of food shortage associated with flood circumstances.